Escalated Force as a Model of Protest Policing: A Case Study of the Rotterdam 2021 Protests - Owczarek, Karolina (HAPSc Policy Briefs Series, 2022)
Since the pandemic outbreak, the Netherlands has been repeatedly gripped by protests over successive restrictions. Protesters were often characterized by aggression and violence, so they had to be demobilized to restore order to the streets. In some cases, the police were forced to use coercive measures. Nonetheless, the November 2021 protest in Rotterdam caused considerable controversy. During the demonstration, gunshots were fired at demonstrators for the first time in a dozen years. This article aims to attribute the strategy of police action during the Rotterdam protests to one of the two models determined by McPhail, Schweingruber, and McCarthy and operationalized by Rak. The study draws on qualitative source analysis and the content analysis technique. The most opinion-forming Dutch news sites, both Dutch- and English-language, were used as sources. These sources were supported by international news sites and channels on the streaming service YouTube. Additionally, the Rotterdam police’s Twitter account and the official politie.nl website were analyzed. A theoretically grounded hypothesis was posited that: during the Rotterdam protests in November 2021, the police, due to the dynamic development of the rally, used a model closer to an escalated force. However, it did not occur in its pure form.